Research advances in energy management and harvesting technologies for autonomous profiling floats - Yuxia Yu; Yuxia Yu; Qunhui Yang; Qunhui Yang; Qunhui Yang; Fuwu Ji; Fuwu Ji; Wei Zhou (Frontiers in Marine Science)
Autonomous profiling floats, such as the Argo floats, predominantly rely on battery power for their energy supply. However, the limited energy storage capacity of batteries imposes significant constraints on their operational lifespan, observation frequency, and the integration of advanced sensors, which has emerged as a critical bottleneck hindering long-term autonomous observations. To address this issue, researchers have explored two primary technical routes: optimizing energy consumption and harvesting energy. This review first systematically analyzes the research progress concerning the energy consumption characteristics of autonomous profiling floats. It then summarizes the key technical strategies and advancements in current energy consumption optimization efforts across four domains: hydraulic system, sensor system, satellite communication system, and control algorithm. Subsequently, the paper reviews the developments and challenges associated with self-powered autonomous profiling floats, with a particular focus on the application of phase-change-material (PCM)-based thermal energy harvesting technology. Finally, the paper proposes that future endeavors should concentrate on advancing energy management and energy development technologies. These include the adoption of Edge Artificial Intelligence (Edge AI) technology for intelligent energy management, flexible solar cells and underwater photovoltaic technologies, Triboelectric Nanogenerator (TENG) technology for wave energy harvesting, novel thermal energy harvesting techniques, and hybrid energy harvesting solutions. By promoting energy diversification and enhancing efficiency, these innovations can strengthen the energy security for autonomous profiling floats and meet the increasing demands for scientific observation.